The equation in slope-intercept form of -y = 3x is y = -3x and slope is -3 and y-intercept is 0
Solution:
Need to write following equation in slope intercept form.
-y = 3x
And determine the slope intercept form.
Slope intercept form of a line is y = mx + c where m = slope and c is constant.
Lets represent –y =3x in slope intercept form.
Multiplying both the sides with -1, we get
-1 x –y = -1 x (3x)
=> y = -3x
On comparing it with y = mx + c , we can say than m = -3 and c = 0 .
Hence slope intercept form of –y = 3x is y = -3x and slope is -3 and y-intercept is 0